Performance, interpersonal relationships and professional satisfaction: determinants to support pharmaceutical reengineering - Fernando de Castro Araújo-Neto; Aline Santana Dosea; Divaldo Pereira de Lyra-Jr (Elsevier, 2024)
Professionalism represents the ethical contract that binds professionals and society. Its technical aspects, such as the professional practice model, form the foundation for attitudinal and behavioral characteristics, including the fiduciary relationship between pharmacists and patients. Despite significant interest in the topic, contextualizing professionalism proves to be a challenging endeavor, relying on collaboration among formal leaders, academics, and practitioners in the field. Consequently, defining, understanding, teaching, and evaluating pharmaceutical professionalism contribute to shape societal perceptions and the understanding of pharmacists and students, who may occasionally struggle to grasp the underlying rationale behind professional practices. Moreover, contextualizing professionalism entails addressing various challenges, such as fostering support for professionalism and its adaptation, which encompasses pharmacists' performance across diverse clinical services, their interpersonal interactions with patients, families, communities, and fellow healthcare professionals, as well as personal job satisfaction amidst obstacles as job insecurity, ethical dilemmas, and compromised autonomy.